(untitled) (Italian Review of Legal History, 2022)
Analyzing a case of habeas corpus discussed at the Bombay Supreme Court of Judicature in 1828, the essay examines the forms of manifestation of power in British India, focusing on a particular feature of the colonial sovereignty: the “extraordinary” nature of the Indian constitution caused the tendential inapplicability to the colonized of what has been defined “the true doctrine of sovereignty and allegiance”, that contemplated not only obligations but also rights and privileges in favor of British subjects. The theme is closely connected with the broader reflection relative to the tension between rule of law and colonial dimension, which refers to the main contradiction inherent to the relationship between the West and the colonies: the “diversity” of the colony and of the colonial subjects justified the perception of the colonial space as “necessarily exceptional”. In the context of British India, the experimentation of the colonial regime took place in substantial contrast with the model of the rule of law, and with the constitution that underpinned it. From this perspective, also the absence of representative institutions and the rejection of the idea of separation of powers were represented by the colonizers as tools of civilization: by identifying the colony as an exceptional space, the very exercise of power in a tendentially despotic sense came to be presented as a remedy aimed at bridging the gap in civilization between the colony and the West. As noted by historiography, there were different levels of “exceptionality”, that corresponded to as many forms of manifestation of power in the colony: in particolar, the exercise of powers through the administrative apparatus was accompanied by the use of “unofficial” practices, based on the physical coercion of colonial subjects. Rather than referring to the colonial system, this second level of power was directed towards individual subjects, aiming to supersede the lack of consensus on the part of the population and to ensure the domination of India. The element of physical coercion was central respect to the exercise of Indian colonial power. In this sense, the exceptionality of the colonial dimension resulted, also, in decentralized and “unofficial” forms of use of force and deployment of authority, where the bodies of the colonized became instruments for the exercise of power: violence and terror were constitutive elements of the Indian rule and of the colonial apparatus, that aimed at the control of local society also by the exercise of forms of coercion on the bodies. This particular conformation of power and sovereignty explains the resistance of the colonial administration towards the application of habeas corpus in favor of the colonized subjects. Being a tool that involved a revision of the subject’s status of liberty, as well as a judicial control over the authority exercised by the East India Company’s officers, the writ of habeas corpus was perceived by the local government as potentially dangerous for the colonial order: the effect of removing the colonized subject, through the order of Crown Courts, from the custody of the colonial officers, was represented as an instrument of destabilization of public peace, also threatening the representation of colonial power as an indivisible and faultless entity. These phenomena were linked to the conflictual relationship between the jurisdiction of the Crown Courts of Justice in India and the Indian government of the East India Company: in the occasion of the case of 1828, the Supreme Court of Judicature of Bombay, that were depended directly by the Crown of England, claimed to apply the principles of British constitution directly in favor of Indian subjects, in contrast with the official position assumed by the local government, that sustained a regime that was in collision with that constitution. The differentiated application of the remedy of habeas corpus, that was a highly symbolic remedy with respect to the theme of personal freedoms, helps to show the fragmentation of the Indian colonial regime and the different degree of interest, on the part of the colonial authorities, in the control of Indian society and population.